Allelopathic intercrops and its mulch as an integrated weed management strategy for rainfed Bt-transgenic cotton hybrids. (September 2020) - Blaise, D.; Manikandan, A.; Verma, P.; Nalayini, P.; Chakraborty, M.; Kranthi, K.R.
Abstract: Weed management in cotton is a major challenge because of the slow initial crop growth. Further, noxious weeds (purple nutsedge: Cyperus rotundus L.) and invasive weeds (smooth joyweed: Alternanthera paronychioides A. St.-Hil.) are difficult to control. Thus, the small and poor farmers of the Indian sub-continent are in need of effective integrated weed management strategies. Intercropping in the wide row space Bt -transgenic cotton hybrids is a possible option to the readily available expensive technologies such as herbicides and polythene mulch. We evaluated 12 different intercrops and its mulching, over 5-years (2014–15 to 2018–19), on weed control, species diversity, seedcotton yield and economics. Intercrops were compared with newspaper or polythene mulch, farmers' practice (FP) and a control. Number of monocot and dicot weeds were the least in the polythene mulched plots and the greatest in the control treatment. Intercrops significantly reduced weed density by 43–71% compared to the control treatment. Intercrops varied in their weed suppression over years, with a consistent weed suppression observed in the sunnhemp plots. Weed biomass was, on an average, reduced by 43% in the sunnhemp plots compared to the FP. High total phenolics and terpenoid content in the above ground parts of sunnhemp possibly contributed to the inhibition of weed seed germination and growth. The top five weeds, in the study area, were Echinochloa colona L., C. rotundus, Urochloa plantaginea (Link.) Hitch., Corchorus trilocularis L. and A. paronychioides . Polythene mulched plots had the highest seedcotton yield but net benefits were the most with sunnhemp intercrop (USD 295.2 ha -1 vs. 176.2 ha -1 for the polythene and 67.2 ha -1 for newspaper mulch) due to reduced input costs. Sunnhemp grown as an intercrop and later mulched can be used as a tool to filter out noxious weeds and provide an effective strategy for integrated weed management. Graphical abstract: Image 1 Highlights: Sunnhemp, among intercrops, an effective tool for weed management. Negligible dominance of purple nutsedge in the sunnhemp intercropped plots. Gross returns maximum in polythene mulch, net benefits highest with sunnhemp intercrop. Polythene mulched plots had the least weed species diversity.